Musika ng Selebrasyong Taytayeno arrangements of heritage band pieces for string ensemble - Roa, Asherine Joanne Matidios; Timbol-Guadalupe, Jocelyn (Diliman, Quezon City U.P. College of Music, 2019)
The proposed study is a music education special project involving the arrangement of heritage band pieces of Banda Uno Malaya from Taytay, Rizal for community string orchestra and a performance that culminates the arrangements. The methodology involved in the study includes survey and research of heritage band repertoire, arrangement in a community youth string orchestra, rehearsal and performance of said arrangements. A compilation of the pieces will be made after the performance.
Thesis (B. M. Music Education) -- University of the Philippines, Diliman.
Keywords: Band music -- Philippines -- Taytay, Rizal; Band music, Arranged